2022
DOI: 10.3389/fmed.2022.973856
|View full text |Cite
|
Sign up to set email alerts
|

The role of the mTOR pathway in diabetic retinopathy

Abstract: The retina, the part of the eye, translates the light signal into an electric current that can be sent to the brain as visual information. To achieve this, the retina requires fine-tuned vascularization for its energy supply. Diabetic retinopathy (DR) causes alterations in the eye vascularization that reduce the oxygen supply with consequent retinal neurodegeneration. During DR, the mammalian target of rapamycin (mTOR) pathway seems to coordinate retinal neurodegeneration with multiple anabolic and catabolic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 160 publications
1
11
0
Order By: Relevance
“…To identify changes in autophagy levels in DR, we assessed changes in expression of autophagy-associated proteins and found that the expression of LC3II/I and Beclin1 in HG-induced ARPE-19 cells was significantly downregulated, whereas the expression of p62 was significantly upregulated, indicating that high glucose inhibited autophagy. As mTOR affects the progression of DR (Casciano et al 2022 ) and Sestrin2 has been implicated in induction of autophagy under stress conditions by inhibiting mTOR (Kim et al 2015 ; Kim and Guan 2015 ), we examined the effects of activating the mTOR pathway on cells over-expressing Sestrin2. Treating ARPE-19 cells with MHY1458, which activates mTOR pathway reversed the protective effects of Sestrin2 over-expression.…”
Section: Discussionmentioning
confidence: 99%
“…To identify changes in autophagy levels in DR, we assessed changes in expression of autophagy-associated proteins and found that the expression of LC3II/I and Beclin1 in HG-induced ARPE-19 cells was significantly downregulated, whereas the expression of p62 was significantly upregulated, indicating that high glucose inhibited autophagy. As mTOR affects the progression of DR (Casciano et al 2022 ) and Sestrin2 has been implicated in induction of autophagy under stress conditions by inhibiting mTOR (Kim et al 2015 ; Kim and Guan 2015 ), we examined the effects of activating the mTOR pathway on cells over-expressing Sestrin2. Treating ARPE-19 cells with MHY1458, which activates mTOR pathway reversed the protective effects of Sestrin2 over-expression.…”
Section: Discussionmentioning
confidence: 99%
“…The upregulation of mTOR activity is likely attributed to elevated circulating levels of insulin, amino acids, and proinflammatory cytokines, indicative of the early endothelial cell injury. 23 Specifically, we observed that EC-C0 contained a higher proportion of functional genes associated with cell migration, cell proliferation, blood vessel development, and angiogenesis ( Figure 3 D). The KEGG pathway analysis demonstrated a strong activation of vascular development and induction of inflammation-related pathways, such as the TNF signaling pathway, FoxO signaling pathway, Rap1 signaling pathway, and Hippo signaling pathway, in the EC-C0 ( Figure 3 E).…”
Section: Resultsmentioning
confidence: 82%
“…Autophagy processes can recycle cytoplasmic organelles and components for eventual tissue remodeling [37,69,86,87,175,177,[207][208][209][210][211][212][213][214][215][216]. There are subtypes of autophagy processing.…”
Section: Cellular Metabolism and The Role Of Apoptosis Autophagy And ...mentioning
confidence: 99%
“…The mechanistic target of rapamycin (mTOR) is a 289-kDa serine/threonine protein kinase that is encoded by a single gene FRAP1 [6,81,87,212,[246][247][248][249]. mTOR also is known as the mammalian target of rapamycin and the FK506-binding protein 12-rapamycin complex-associated protein 1 [222].…”
Section: A Central Role For the Mechanistic Target Of Rapamycin (Mtor...mentioning
confidence: 99%
See 1 more Smart Citation